2020
DOI: 10.1007/s10393-020-01498-5
|View full text |Cite
|
Sign up to set email alerts
|

Cultural Values and the Coliform Bacterial Load of “Masato,” an Amazon Indigenous Beverage

Abstract: Access to safe drinking water is limited in many isolated areas, such as the Amazon where Indigenous peoples frequently reside. Identifying safe forms of drinking water accepted by the communities could have positive health benefits for Indigenous peoples. Many Amazon Indigenous peoples traditionally prepare and consume a fermented beverage called masato, which is frequently the only form of water consumption. Despite its widespread consumption and evidence of the health benefits of fermentation, masato remain… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 32 publications
0
7
0
Order By: Relevance
“…Drinking masato , a beverage made typically from fermented cassava tuber ( Manihot esculenta ) (Sedano Bautista, 2006), is a common practice in Indigenous Amazonian communities and may also be a gendered pathway for H. pylori transmission. Masato is typically made by women, who chew and spit boiled cassava into a vat containing water, which is then left to ferment into a mildly alcoholic beverage (Bussalleu et al, 2020). Enzymes in the saliva aid in the fermentation process and microbiological analyses of masato have shown that this beverage has multiple strains of Lactobacillus (Colehour et al, 2014) and that the fermentation process may eliminate E. coli that is present in communal water sources (Bussalleu et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…Drinking masato , a beverage made typically from fermented cassava tuber ( Manihot esculenta ) (Sedano Bautista, 2006), is a common practice in Indigenous Amazonian communities and may also be a gendered pathway for H. pylori transmission. Masato is typically made by women, who chew and spit boiled cassava into a vat containing water, which is then left to ferment into a mildly alcoholic beverage (Bussalleu et al, 2020). Enzymes in the saliva aid in the fermentation process and microbiological analyses of masato have shown that this beverage has multiple strains of Lactobacillus (Colehour et al, 2014) and that the fermentation process may eliminate E. coli that is present in communal water sources (Bussalleu et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…The lack of a seasonal approach, including quantitative and qualitative data collection, represents a limitation in this study. We have previous studies 28 , 76 , 96 with this same population that are helping us to understand seasonal changes that we plan to use to triangulate our results.…”
Section: Discussionmentioning
confidence: 99%
“…For example, Indigenous knowledge about edible wild species is key to enhancing dietary diversity 13 , including during extreme climatic events 74 . Practices of traditional food preparations such as fermented foods provide safe and culturally accepted edible options to community members within the Shawi and among other populations 75 , 76 . Given that anaemia is also a result of other health conditions like intestinal parasites, chronic inflammation, and excessive bleeding related to pregnancy, adequate access to health care services may decrease the probability of having anaemia while simultaneously increasing the adaptive capacity of our participants to respond to climatic risks that threaten their health 77 .…”
Section: Qualitative Studymentioning
confidence: 99%
“…In the Peruvian case, there is scarce information in the scientific literature about the manufacture practices of some of their traditional products [32]. In the case of the two beverages studied in our work, a photographic study about the "Masato de Yuca" manufacture was recently reported [33]; this was coincident with the process flow diagram (see supplementary Fig. S1) collected from the communities of Chanchamayo and Satipo that contributed to our study, although in our case commercial samples were collected which did not use human saliva for their preparation (Table 1).…”
Section: Traditional Uses Of Vegetables As Peruvian Intangible Cultural Heritagementioning
confidence: 94%